Os colono só trabalha [...] : a Colônia Rio Uruguay : aspectos da atuação das companhias colonizadoras entre 1920-50 - Comassetto, Carlos Fernando (2008)
The growing of the Capitalism system in Europe was the main reason of the internal migration and the transoceanic crossing of workers mainly those from rural areas to America. In Brasil the bill of Lands from 1850 to 1854 end the cycle of free landing from Federal government and created the real state speculations. In the early XX Century, the occupation of the territory of Santa Catarina state occurred mainly by private colonization companies, which measured the land and sell pieces of land. The commercialization of such lands follows the Capitalism system of accumulation of wealthy. The main purpose of this project is to study the way of the colonization companies acted and the migratory movement that occupy the whole region of the Alto Uruguai of the Santa Catarina state between 1920 and 1950 by land workers, which focus analysis, is the Colonia Rio Uruguay